Bulletin / Comité Socialiste pour la Palestine Ouvrière
Ed.allem.: Bulletin. Socialistisches Komitee fuer das arbeitende Palastina. (ZK 16235). - Ed. angl.: Bulletin. International socialist committee for the organized Jewish workers in Palestine. (ZK 16236).